Inositol pyrophosphates promote the interaction of SPX domains with the coiled-coil motif of PHR transcription factors to regulate plant phosphate homeostasis - Martina K. Ried (Nature Portfolio, 2021)
Plants regulate phosphate homeostasis via the interaction of PHR transcription factors with SPX receptors bound to inositol pyrophosphate signaling molecules. Here the authors show that inositol pyrophosphate-bound SPX interacts with the coiled-coil domain of PHR, which regulates the oligomerization and activity of the transcription factor.